MAINTAINING THE CONTINUITY OF WATER RESOURCES THROUGH THE CONSERVATION OF PROTECTED FORESTS IN LARIKE VILLAGE, WEST LEIHITU DISTRICT, CENTRAL MALUKU REGENCY - Parera, Evelin; Putuhena, Jusmy D.; Parera, Lydia R. (LPPM Univ. Ibn Khaldun Bogor, 2025)
Protected forests play a role in guarding a balanced ecosystem and water resilience by supporting cycle hydrology and preventing the degradation of the environment. However, the low public awareness regarding the importance of forest protection Still becomes a challenge in effort conservation. Research This aims to analyze the effective method of socialization in increasing understanding, attitudes and behaviour of the Larike Village community-related preservation of forest protection as an effort to guard against water resistance. The method used covers discussion group focused (FGD), seminars, training conservation land and water, as well as campaigns through digital media. Evaluation is done through pre-tests and post-tests to measure the change level of public understanding. Research results show an improvement in public understanding from 30% before socialization to 85% after socialization, as well as a change in attitude positive from 40% to 88%. In addition, the behaviour of society in effort conservation increased from 29% to 82%. The conclusion of the study This is that method systematic and community-based socialization participation can increase awareness as well as community involvement in the preservation of forest protection use guard resilience source water power​ sustainability.